GlmU inhibitor from the roots of Euphorbia ebracteolata as an anti-tuberculosis agent. Issue 28 (22nd June 2022) - Han, Xiuyan; Chen, Changming; Wang, Honglei; Kang, Jian; Yan, Qiulong; Ma, Yufang; Wang, Wenxin; Wu, Shan; Wang, Chao; Ma, Xiaochi
Abstract : Ebractenoid F was identified to be a GlmU inhibitor from Euphorbia ebracteolata, which could inhibit the cell wall biosynthesis of M. tb H37Ra, along with the biofilm formation. Abstract : At present, the emerging drug-resistance of Mycobacterium tuberculosis ( M. tb ) against existing frontline drugs has prompted the development of novel anti-tuberculosis agents based on new targets. Activity of the bifunctional enzyme, glucosamine-1-phosphate acetyltransferase activity and N -acetylglucosamine-1-phosphate uridyltransferase (GlmU) is essential for biosynthesis of the mycobacterium cell wall components and has been proposed as a potential drug target for therapeutic interventions. On the basis of the high-throughput screening of the GlmU AT inhibitor, an extract of Euphorbia ehracteolata displayed a significant inhibitory effect among 49 tested herbal medicines. Using the bioassay-guided separation, an aromatic diterpenoid ebractenoid F was identified as a GlmU AT inhibitor (IC50 : 4.608 μg mL −1 ). Inhibition kinetics showed that ebractenoid F acted as a competitive inhibitor for substrate acetyl-CoA and an uncompetitive inhibitor for substrate GlcN-1-P. Ala434 was deduced to be the key active residue for the interaction between ebractenoid F and GlmU. Furthermore, ebractenoid F displayed an anti-mycobacterial effect against M. tb H37Ra with a minimal inhibitory concentration (MIC) of 12.5 μg mL −1 along with an inhibitory effect on the formation of biofilm and a synergistic effect with isoniazid against M. tb H37Ra. Above all, a GlmU inhibitor was identified from E. ehracteolata and is proposed to be a potential therapeutic anti-tumberculosis agent.